Intergenerational Practice: Mentoring and social capital for twenty-first century communities of practice - Cumming-Potvin, Wendy; MacCallum, Judith (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
Aiming to elucidate the relationship between social capital and intergenerational practice within mentoring, this article presents data from a case study of the School Volunteer Program in Western Australia. Drawing on situated learning theory and the concept of community of practice (Lave & Wenger, 1991; Wenger, 1998; Wenger, McDermott, & Snyder, 2002), the discussion examines benefits and limitations of intergenerational practice. Results acknowledge the potential for intergenerational practice to build social capital for both mentees and mentors. However, further research is required to examine mentoring in school-based communities of practice where complex issues of power (see Bourdieu, 1985) may empower or restrict student voices.